Development of MICADO (Local Wisdom-Based Module) to Improve The Ability of Conceptive Comprehension V-Grade Students - Pengembangan MICADO (Modul Berbasis Local Wisdom) untuk Meningkatkan Kemampuan Pemahaman Konsep Siswa Kelas V - Sari, Irena Rafika; Hilyana, F Shoufika; Fardani, Much Arsyad (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2023)
Teaching materials that are monotonous and unattractive, as well as the lack of innovation in teaching materials, can affect students' ability to understand concepts to be low. The purpose of this research is to improve students' conceptual understanding abilities through MICADO (based module local wisdom) on Mathematics content with material on cubes and blocks. This research is research and development (Research and Development), using a model adapted from Sugiyono, which consists of 10 steps. In this study, it was only carried out up to the design improvement stage. The stages are 1) identification of potential and problems 2) information gathering 3) product design 4) design validation 5) design improvement 6) trial use of limited scale 7) design improvement. Data collection techniques include interviews, questionnaires, and documentation. In this study, the material expert validation test obtained an average of 82, 2% with very good eligibility criteria. In this study, the material expert validation test obtained an average of 82, 5% with very good eligibility criteria. Based on the results of the validation obtained an average of 98, 75% with very good eligibility criteria. Based on the results of the validation obtained, it can be stated that MICADO (module based on local wisdom) is suitable for use by fifth-grade students to improve their ability to understand concepts.Keywords: Local Wisdom, MICADO, Concept UnderstandingBahan ajar yang monoton dan kurang menarik, serta kurangnya inovasi bahan ajar dapat mempengaruhi kemampuan pemahaman konsep siswa menjadi rendah.Tujuan penelitian ini untuk meningkatkan kemampuan pemahaman konsep siswa melelalui MICADO (modul berbasis local wisdom) pada muatan Matematika dengan materi bangun ruang kubus dan balok. Penelitian ini merupakan penelitian dan pengembangan (Reasearch and Development), dengan menggunakan model yang diadaptasi dari Sugiyono, yang terdiri dari 10 langkah. Pada penelitian ini hanya dilakukkan hingga tahap perbaikan desain. Adapun tahapnya, yakni 1) identifikasi potensi dan masalah 2) pengumpulan informasi 3) desain produk 4) validasi desin 5) perbaikan desain 6) uji coba pemakaian skala terbatas 7) perbaikan desain. Teknik pengumpulan data meliputi wawancara, angket, dan dokumentasi. Pada penelitian ini, uji validasi ahli materi memperoleh rata-rata 82, 5% dengan kriteria kelayakan sangat baik, uji validasi ahli media memperoleh rata-rata 98, 75% dengan kriteria kelayakan sangat baik. Berdasarkan hasil validasi yang diperoleh, maka dapat dinyatakan MICADO (modul berbasis local wisdom) layak untuk digunakan siswa kelas V untuk meningkatkan kemampuan pemahaman konsep.Kata kunci: Local Wisdom, MICADO, Pemahaman Konsep